ARABIC: AN AFRICAN COMMON HERITAGE - Dr. Busari Kehinde Kamorudeen (International Research Journal of Arabic and Islamic Studies, 2021)
From its inception. Arabic has influenced Nigerian languages. It has impacted positively on their ideas, thoughts and research. Languages like Yoruba, Hausa and Fulfulde borrowed some Arabic vocabularies which unveiled their resemblance with Semitic languages. Before the arrival of the colonialists, some Nigerian languages adopted the practice of writing their languages in Arabic script which is called ‘Ajami’. Islam served as a vehicle by which Arabic reached several parts of the world. Being the language of the scripture of Islam, it has always been regarded as inherent part of the religion of Islam. Arabic, which is the mother tongue of many Africans, is taught in many schools and Universities as an important language studied by Muslims and non-Muslims without diminishing the fact that it possesses both social and spiritual significance. The links of Hausa with Arabic, as a language, and Islam, as a religion have always given room for the former to boost its linguistic structure and cultural status in Nigeria. The influence of Arabic on both Hausa and Yoruba is two-fold. Firstly, is the diffusion of Arabic loan-words into these languages, and secondly, is the development of writing system along the lines of the Arabic script long before the Latin script was introduced in Nigeria. This paper examines Arabic as a common African heritage that influenced most African languages in general and Nigerian languages in particular via a qualitative research methodology.